Terrorism in cyberspace: challenges in planning and executing political violence online - Jacobsen, Jeppe Teglskov (Politica, 2015)
The Internet is often presented as a devastating tool in the hands terrorists. This is a truth in need of modification. Drawing on insights from studies of Sunni extremists, Breivik and Anonymous, the article assesses claims about terrorists’ use of the Internet in planning and executing political violence. It finds, first, that the anarchical, anonymous Internet spurs mistrust and fragmentation, rendering it more, not less difficult for terrorists to maintain a coherent strategy. Second, the article notes how most violent individuals seek real life interactions, guns and explosions rather than organize terrorism online or hacking in solitude behind a computer screen. It is primarily the socially marginalized who find the Internet appealing in organizing and executing terrorism.